# What is (4x-3)^2= (3x+1)^2+x^2

Question asked by: neurology

Asked on: 21 Nov 2009

(4x-3)^2= (3x+1)^2+x^2

(4x-3)(4x-3) is 16x^2 -24x + 9

(3x+1)(3x+1) is 9x^2 + 6x + 1

By: knowitall

Replied at: 22 Nov 2009

Rate Answer

**Comment or provide your answer to this question**

### Comments and other answers:

(4x-3)^2 = (3x+1)^2 + x^2
Or, 16x^2 – 24x + 9 = 9x^2 + 6x + 1 + x^2
Or, 6x^2 – 30x + 8 = 0
Or, 3x^2 – 15x + 4 = 0
Or, x = [-(-15)(+/-)√{(-15)^2 – 4*3*4}]/2*3
Hence, x = 4.717 or, x = 0.2826

By: psahu63

By: psahu63

*Date of comment: Wed, Sep 8th 2010*
Hello, i need to find the value of x. that is only half bit u have explained. and i have already got to that point. at the end i come up with 6x^2-30x+8=0
i need to get the value of x. i tried the quadratic formula, a(x+p)^2+r formul, (x+p)(x+q) formula but none of them give me the correct answer whihc is
x=7

By: neurology

By: neurology

*Date of comment: Sun, Nov 22nd 2009***Ask a New Question**

Find out more about Maths

Maths Questions and Answers

algebra Questions and Answers

Next question: Abandon rate

**Become a Member! It's Free >>>**

**Share on Facebook:**
**On Twitter:**
Tweet this!
**More Questions:**

Maths-algebra

Volume Of Curve Rotated Around X-axis

By Poisson Random Variable

Find The Value Of X Which Gives Sinx=logx

Maths Fraction Question